Associations between Exposure to Tobacco Smoke and Behavioral Problems in Preschool Japanese Children. (14th May 2020) - Wada, Keiko; Ueyama, Jun; Konishi, Kie; Goto, Yuko; Koda, Sachi; Mizuta, Fumi; Tamura, Takashi; Watanabe, Kaori; Ando, Kyoko; Kondo, Takaaki; Nagata, Chisato
Abstract : Background . A few studies related to pediatric behavior have measured secondhand smoke exposure in children using valid objective biochemical markers. We aimed at investigating the associations between current and cumulative exposure to tobacco smoke, measured both subjectively and objectively, and behavioral problems in children. Methods . Subjects were 437 Japanese children, aged 3–6 years in 2006. Exposure to tobacco smoke was evaluated from a parent-administered questionnaire and urinary cotinine concentrations. The cotinine concentrations were measured using first-void morning urine by liquid chromatography-tandem mass spectrometry. Children's behaviors were assessed by the parent-completed Strengths and Difficulties Questionnaire. Results . After multiple adjustments for covariates, higher total difficulty scores of children were significantly associated with the larger number of cigarettes parents smoke, more smokers among cohabiters, and more pack-years of exposure to tobacco smoke from parents and cohabiters. The total difficulty scores were 8.72, 9.09, and 10.52, respectively, for children in the low, middle, and high tertiles of creatinine-corrected cotinine concentrations in urine (p = 0.002, trend p = 0.005 ). There was no substantial sex difference in the positive associations between passive smoking and the SDQ scores. Conclusions . Exposure to tobacco smoke in early childhood may be involved in the development of pediatric behavioral problems. The importance of reducing the exposure of children to tobacco smoke, particularly in the home, was further emphasized for the prevention of psychological and behavioral problems in childhood.